Switching to the single-tablet regimen of elvitegravir, cobicistat, emtricitabine, and tenofovir DF from non-nucleoside reverse transcriptase inhibitor plus coformulated emtricitabine and tenofovir DF regimens: Week 96 results of STRATEGY-NNRTI. Issue 4 (4th July 2017) - Pozniak, Anton; Flamm, Jason; Antinori, Andrea; Bloch, Mark; Ward, Douglas; Berenguer, Juan; Cote, Pierre; Andreatta, Kristen; Garner, William; Szwarcberg, Javier; Nguyen-Cleary, Thai; McColl, Damian J.; et al.
Abstract : Background: HIV-1-infected, virologically suppressed adults wanting to simplify or change their non-nucleoside reverse transcriptase inhibitor (NNRTI)-based regimens may benefit from switching to the single-tablet regimen of elvitegravir, cobicistat, emtricitabine, and tenofovir disoproxil fumarate (E/C/F/TDF). Objective: We examined differences in the proportion of participants with HIV-1 RNA < 50 copies/mL (Snapshot analysis), change in CD4 cell count, safety, and patient-reported outcomes in participants switching to E/C/F/TDF from an NNRTI + FTC/TDF (TVD) regimen. Methods: STRATEGY-NNRTI was a 96-week, phase 3b, randomized, open-label, study examining the efficacy, safety, and tolerability of switching to E/C/F/TDF in virologically suppressed individuals (HIV-1 RNA < 50 copies/mL) on an NNRTI + TVD regimen. Participants were randomized to switch or remain on their NNRTI-based regimen (no-switch). Results: At Week 96, 87% (251/290) of switch and 80% (115/143) of no-switch participants maintained HIV-1 RNA < 50 copies/mL (difference 6.1%; 95% CI −1.3 to 14.2%; p  = 0.12) according to the FDA-defined snapshot algorithm. Both groups had similar proportions of subjects with virologic failure (2.8% switch, 1.4% no-switch). Discontinuations resulting from adverse events were infrequent (3% [9/291] switch, 2% [3/143] no-switch). Three switch participants (1%) discontinued due to renal adverse events (2 of the 3 before Week 48). Switch participants reported significant improvements in neuropsychiatric symptoms by as early as Week 4, and which were maintained through Week 96. Conclusions: E/C/F/TDF is safe and effective and reduces NNRTI-associated neuropsychiatric symptoms for virologically suppressed HIV-positive adults switching from an NNRTI plus FTC/TDF-based regimen.